Drug utilization and medication costs at the end of life. (3rd March 2016) - Pont, Lisa; Jansen, Kristian; Schaufel, Margrete Aase; Haugen, Dagny Faksvåg; Ruths, Sabine
ABSTRACT: In the end stages of life, drug treatment goals shift to symptom control and quality of life and as such changes in drug utilization are expected. The aim of this paper is to review the extent to which costs are considered in drug utilization research at the end of life, with a particular focus on the outcome measures being used. This systematic review identified seven studies across varied settings studies reporting both drug utilization and medication cost outcome measures. The main factors identified that impacted medication use and cost were the time period considered and the provision of specialist palliative care services. Combining drug utilization and medication cost outcomes is critical for the allocation of healthcare resources and the development of a sound health policy.